Pembaharuan Muatan Pendidikan Mata Pelajaran Bahasa Arab di Sekolah Menengah Pertama Islam di Indonesia - Rodhy Harisca (Jurnal Internasional Pendidikan Bahasa Arab, 2023)
The Arabic subject contents at Islamic intermediate schools in Indonesia are still need to be developed. This is necessary in order to support and achieve the Arabic learning objectives in Indonesia. As Arabic subjects are mostly popular and studied in every Islamic intermediate schools in Indonesia, especially in Islamic intermediate schools where there are dormitories. The purpose of this article is to construct the educational content renewal of Arabic language subject at Islamic intermediate schools in Indonesia for the sake of Arabic learning objectives achievement in Indonesia. The article used the descriptive analytics method as the research construct the educational content renewal of Arabic language subject at Islamic intermediate schools in Indonesia by using the questionnaire, interview and observation tool, which clarifies the content of the Arabic language courses in the currently used curriculum, in order to construct the suitable Arabic contents. The result of this article is the Arabic language subject contents would make listening skill and speaking skill as the Arabic study plans at Islamic intermediate schools in Indonesia. Based on the findings, the author recommended the need to choose the supporting educational contents and appropriate courses in order to obtain the educational goals in teaching the Arabic language at the intermediate stage in Indonesia, with the provision of modern digital teaching aids of all kinds so that teaching the Arabic language becomes an interesting and effective process. Then finding a teacher's guide or teacher's guide to facilitate the education process.